The Chronicles of Propaganda: Hegemony, the Paladin, and the Christian-Hero’s Journey - Caravella Castillo, Maya (Journal of Artistic Creation and Literary Research, 2025)
This essay analyses the propagandistic nature of C. S. Lewis’ The Chronicles of Narnia: The Lion, the Witch, and the Wardrobe in order to refute the misinterpretation that sets children’s literature as naïve and plain. Framed in the context of the Cold War, this propaganda focuses on pro-Britain and anti-communist messages aimed at supporting the idea of Britain as a hegemonic power. Through a multidisciplinary approach involving Myth Criticism and Cultural Studies, this paper revises the concept of myth as a tool for propaganda. In doing so, it proposes a structure which has been termed “Meta-Meta-Mythic Structure.” This includes three interconnected levels of Myth which sustain and advertise each other. These levels consist of a Modern Myth (Britain’s hegemonic power), a Fallacious Myth (Britain as paladin of democracy and freedom), and Classical Myths (the biblical myth and the hero’s journey). The analysis of Lewis’ novel deals with the projection of the classical myths as conveyors of the fallacy, reaching the child-reader’s unconscious and conditioning their perception and understanding of the world. As a result, the dissolution of propaganda through the Meta-Meta- Mythic Structure will be proven effective.